2019
DOI: 10.32615/bp.2019.075
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antioxidant enzyme activities and respective gene expressionsin potato somatic hybrids under NaCl stress

Abstract: Potato (Solanum tuberosum L.), a plant of great economic importance worldwide, is known to be highly sensitive to salinity. Improving the tolerance of this crop was envisaged using interspecific somatic hybridization. In this report, the impact of salinity on three hybrid lines (STBa, STBc, and STBd) produced by protoplast fusion between the cv. BF15 and the wild species Solanum berthaultii was investigated in vitro. An analysis of plant response to oxidative stress was considered when plantlets were submitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Interestingly, CAT activity was not increased in our study. However, the previous studies have shown that CAT activity was significantly increased in salt-tolerant potatoes [44]. We speculated that SOD and POD might play a major role in our salt-tolerant varieties.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, CAT activity was not increased in our study. However, the previous studies have shown that CAT activity was significantly increased in salt-tolerant potatoes [44]. We speculated that SOD and POD might play a major role in our salt-tolerant varieties.…”
Section: Discussionmentioning
confidence: 81%
“…The increase in RDM and R/S ratio observed in the present study may also be related to the beneficial effect of applying H 2 O 2 in adequate concentrations, which significantly increases tolerance to oxidative stress caused by salinity, increasing the antioxidant status of the plant cells and tissues [ 35 ], as well as changes in gene expression, transport of sugars and phytohormones [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Delikat and Rasant. The genes were present also in BC1 and BC2 progenies and resistance to late blight Oxidative stress responses [183] NS -not specified.…”
Section: Use Of Cell Fusion Between Potato Crop and Its Wild Relatives For Resilient Potatomentioning
confidence: 99%